The Importance of a Country to the Students’ Geographical Interest: The Results of an Empirical Investigation - Hemmer, Michael (Journal of Geography Education, 2003)
Within the framewerk of an empirical investigation more than two thousand German schoolchildren ofthe years 8 to 13 were questioned about their geographical interest in the USA and in the CIS. It becomes apparent that in teaching geography there are almost identical fields of interest in the above-mentioned nations with regard to specific themes and working methods. However, a comparison between the data concerning the USA and the CIS gained from the analyses demonstrates that the students’ geographical interest in the CIS. Consequently, the region has a far greater influence on the students’ interest than has ever been assumed. Particularly, there is an urgent need for action in view of countries with an Eastern bloc-image.